PERSEPSI PEGAWAI TERHADAP KEPEMIMPINAN ATASAN LANGSUNG DI DINAS PENDIDIKAN KABUPATEN PASAMAN BARAT - Desma Warni (Universitas Negeri Padang, 2014)
This study discusses about the employee's perception of the immediate supervisor's leadership in the West Pasaman Department of Education, with the aim of the study was to obtain information about how the employee's perception of the immediate supervisor's leadership in the Education Department of West Pasaman with aspects affect, empower, motivate and maintain cooperative relationships. The study population were employees of Education Department of West Pasaman totaling 66 people, sampling studies using Krejci table with the number 56. The results of the study using a questionnaire measuring instruments for the indicators obtained average influence (3.4) empower (3.4) 3.1 motivate and discipline (3.5) with an overall average (3.35). This indicates that the direct supervisor's leadership in the Education Department of West Pasaman good enough Keywords: Leadership Tops Direct